Degradation of Antibiotics by Fenton-like Reaction Catalyzed by Iron Oxide - Junqing You; Xihui Zhang; Jinglei Chen (Advances in Materials Science and Engineering)
In recent years, antibiotics have been widely used in the treatment of human and animal diseases due to their effectiveness. Most antibiotics enter the environment in the form of primitive or metabolites, making them new environmental pollutants, destroying the ecological environment, and endangering human health. The Fenton method is one of the advanced oxidation technologies including the traditional Fenton method and various Fenton methods. It has a good effect on the degradation of antibiotics in wastewater. Among them, the Fenton-like method has been widely studied by scholars because of its wide pH reaction conditions and better degradation efficiency. This article takes the Fenton-like reaction as the research object to study the catalytic and promotion effect of iron oxide as a catalyst on the degradation of antibiotics in the Fenton-like reaction. The experimental results show that the iron oxide catalytic system is much better than the traditional ferrous ion-catalyzed Fenton system to degrade antibiotics. Under certain experimental conditions, the degradation rate of ofloxacin in the Fe3O4-H2O2 reaction system for 72 hours reached 79.3%.